2023
DOI: 10.1126/sciadv.adg5690
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the structural dynamics in molten salt–promoted MgO-based CO 2 sorbents and their role in the CO 2 uptake

Abstract: The development of effective CO 2 sorbents is vital to achieving net-zero CO 2 emission targets. MgO promoted with molten salts is an emerging class of CO 2 sorbents. However, the structural features that govern their performance remain elusive. Using in situ time-resolved powder x-ray diffraction, we follow the structural dynamics of a model NaNO 3 -promoted, MgO-based CO 2 sorbent. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…One hypothesis to explain the changes observed in the Na K-edge XANES spectra upon carbonation could be the decomposition of NaNO 3 , e.g., into NaNO 2 or Na 2 O which would transform further under carbonation conditions (CO 2 , 315 °C) to sodium-containing carbonates Na 2 CO 3 and/or Na 2 Mg­(CO 3 ) 2 , as previously observed . However, according to Rekhtina et al, the decomposition of NaNO 3 does not take place below 450 °C.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…One hypothesis to explain the changes observed in the Na K-edge XANES spectra upon carbonation could be the decomposition of NaNO 3 , e.g., into NaNO 2 or Na 2 O which would transform further under carbonation conditions (CO 2 , 315 °C) to sodium-containing carbonates Na 2 CO 3 and/or Na 2 Mg­(CO 3 ) 2 , as previously observed . However, according to Rekhtina et al, the decomposition of NaNO 3 does not take place below 450 °C.…”
Section: Resultsmentioning
confidence: 74%
“…One hypothesis to explain the changes observed in the Na K-edge XANES spectra upon carbonation could be the decomposition of NaNO 3 , e.g., into NaNO 2 or Na 2 O which would transform further under carbonation conditions (CO 2 , 315 °C) to sodium-containing carbonates Na 2 CO 3 and/or Na 2 Mg(CO 3 ) 2 , as previously observed. 42 However, according to Rekhtina et al, the decomposition of NaNO 3 does not take place below 450 °C. Also, Na 2 CO 3 and Na 2 Mg(CO 3 ) 2 could only be formed over repeated carbonation and regeneration ( T ≥ 450 °C) cycles through the partial decomposition of NaNO 3 and the carbonation of the decomposition products, as previously observed by Rekhtina et al 42 Since the carbonation temperature was considerably below the decomposition temperature (315 °C), NaNO 3 decomposition is not expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ads system substrate adsorbate (5) where E system represents the total energy of the adsorbate adsorbed on the substrate. E substrate refers to the energy of the substrate (pure MgO and NaNO 3 coadsorption with MgO).…”
Section: Methodsmentioning
confidence: 99%
“…With the continuous concern of people on global climate change, CO 2 capture, as an important means to reduce carbon emissions, has received extensive attention from countries around the world. Compared with high-temperature CO 2 capture adsorbents such as CaO, , Na 4 SiO 4 , , Li 4 SiO 4 , , and ZrSiO 4 , MgO is considered a potential CO 2 capture material because of its wide range of sources, low application temperature (200–400 °C), and high theoretical CO 2 adsorption capacity (110 wt %). Although MgO has broad application potential in CO 2 capture at intermedium temperature, its actual adsorption capacity (<0.5 mmol/g) is small because of its small specific surface area and slow reaction kinetics . In addressing this problem, Harada and co-workers confirmed that alkali metal nitrate/nitrite doping can significantly improve the performance of MgO for CO 2 adsorption. , Gao et al prepared a series of MgO-based adsorbent materials doped with MNO 3 /NO 2 (M = Li, Na, and K) and demonstrated that NaNO 3 was the key substance contributing to the enhanced adsorption capacity of MgO.…”
Section: Introductionmentioning
confidence: 99%